Technical and Economic Feasibility of Sensor Technology for Health/Environmental Condition Monitoring - Karim A.N.M.; Nordin A.N.; Begum S. (Elsevier Ltd, 2023)
Similar to any other technology, the application of sensors in ubiquitous health and environmental condition monitoring is sustained depending on their performance. The scope of manufacturing low-power microelectronics; the miniaturization, design, and development of sensor material; and the fabrication of intricate and delicate shapes have led to the realization of intelligent systems for health and environment monitoring purposes. With the advancement of materials science and technology coupled with the enormous opportunities from wireless networking and the Internet, the scope of sensor application has widened extensively. However, ambitious initiatives such as wireless monitoring systems will gain a competitive edge if the systems can be operated economically with reliable technical performance. © 2014 Elsevier Ltd All rights reserved.